Alox12/15 Deficiency Exacerbates, While Lipoxin A4 Ameliorates Hepatic Inflammation in Murine Alcoholic Hepatitis - Queck, Alexander; Fink, Annika F.; Sirait-Fischer, Evelyn; Rüschenbaum, Sabrina; Thomas, Dominique; Snodgrass, Ryan G.; Geisslinger, Gerd; Baba, Hideo A.; Trebicka, Jonel; Zeuzem, Stefan; Weigert, Andreas; Lange, Christian M.; et al. (Frontiers in Immunology, 2020)
Alcoholism is one of the leading and increasingly prevalent reasons of liver associated morbidity and mortality worldwide. Alcoholic hepatitis (AH) constitutes a severe disease with currently no satisfying treatment options. Lipoxin A4 (LXA4), a 15-lipoxygenase (ALOX15)-dependent lipid mediator involved in resolution of inflammation, showed promising pre-clinical results in the therapy of several inflammatory diseases. Since inflammation is a main driver of disease progression in alcoholic hepatitis, we investigated the impact of endogenous ALOX15-dependent lipid mediators and exogenously applied LXA4 on AH development. A mouse model for alcoholic steatohepatitis (NIAAA model) was tested in Alox12/15+/+ and Alox12/15-/- mice, with or without supplementation of LXA4. Absence of Alox12/15 aggravated parameters of liver disease, increased hepatic immune cell infiltration in AH and elevated systemic neutrophils as a marker for systemic inflammation. Interestingly, i.p. injections of LXA4 significantly lowered transaminase levels only in Alox12/15-/- mice and reduced hepatic immune cell infiltration as well as systemic inflammatory cytokine expression in both genotypes, even though steatosis progressed. Thus, while LXA4 injection attenuated selected parameters of disease progression in Alox12/15-/- mice, its beneficial impact on immunity was also apparent in Alox12/15+/+ mice. In conclusion, pro-resolving lipid mediators may be beneficial to reduce inflammation in alcoholic hepatitis.